Hoffmann Photograph MS608_3_19_001 - Owen, Walter E., 1896-1963 (My University, 2013)
Black and white group photo of Gertrude and others at a party. Subjects identified on reverse.

Handwriting identifying subjects: "From left to Right | Charles Weidman | G. Hoffmann | Ruth St Denis | Doris Humphrey | Hosea Limou"; location, etc. Also includes Walter E. Owen stamp.
Keywords: Hoffmann, Gertrude